ETL Data conversion: Extraction, transformation and loading Data conversion (International Journal of Engineering and Computer Science, 2017)
The essential elements of decision support system are data warehousing and on-line analytical processing (OLAP), which are focus of the database industry. Recently, many commercial products and services are database management system vendors. Decision support places some rather different requirements on database technology compared to traditional on-line transaction processing applications. The researchers and developers had proposed various trials on new requirements of data warehousing and OLAP technologies to put a standard conceptual design of ETL processes in data warehouse. To avoid limitations of the previous trials, the author proposed: 1. The model for conceptual design of ETL processes and entity mapping diagram (EMD), which is built upon the enhancement of the models to support some missing mapping features. 2. The conceptual model in a prototype called EMD Builder and uses it in an illustration scenario. This is an ETL project,, which focuses on data transformation and loading in Oracle Data warehouse. Extraction–transformation–loading (ETL) tools are pieces of software responsible for the extraction of data from several sources, its cleansing, customization, reformatting, integration, and insertion into a data warehouse. Structure the ETL development be potentially one of the major tasks of construction a warehouse; it is difficult, time consuming, and consume most of data warehouse project’s implementation efforts, costs, and resources. In spite of the importance of ETL processes, little research has been done in this area due to its complexity. There is a apparent lack of a ordinary sculpt that can be used to be a symbol of the ETL case scenarios. In this paper we will try to navigate through the efforts done to conceptualize the ETL processes. These projects try to represent the main mapping activities at the conceptual level. Due to the differences and variation stuck between the planned solutions for the intangible design of ETL processes and due to their limitations, this paper also will propose a model for conceptual design of ETL processes. The proposed model is built upon the enhancement of the models in the previous models to support some missing mapping features.